2023
DOI: 10.3233/jad-220721
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells in the Treatment of Alzheimer’s Disease: Current Status, Challenges, and Future Prospects

Abstract: Alzheimer’s disease (AD), a progressive dementia, is one of the world’s most dangerous and debilitating diseases. Clinical trial results of amyloid-β (Aβ) and tau regulators based on the pretext of straightforward amyloid and tau immunotherapy were disappointing. There are currently no effective strategies for slowing the progression of AD. Further understanding of the mechanisms underlying AD and the development of novel therapeutic options are critical. Neurogenesis is impaired in AD, which contributes to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…In rodent models affected by alkaline neurotoxicity, the transplantation of human NSCs with high choline acetyltransferase expression has been seen to reverse deficits in spatial memory and learning [68]. In other studies, NSCs are shown to have the potential to protect cerebral capillaries, reduce Aβ and tau pathologies, decrease inflammation, and enhance neurogenesis (Figure 9) [32]. Another study further demonstrated that transplanted human NSCs in the brains of mice effectively reduce Tau phosphorylation levels [74].…”
Section: Stem Cell Treatment For Alzheimer 'S Diseasementioning
confidence: 90%
See 1 more Smart Citation
“…In rodent models affected by alkaline neurotoxicity, the transplantation of human NSCs with high choline acetyltransferase expression has been seen to reverse deficits in spatial memory and learning [68]. In other studies, NSCs are shown to have the potential to protect cerebral capillaries, reduce Aβ and tau pathologies, decrease inflammation, and enhance neurogenesis (Figure 9) [32]. Another study further demonstrated that transplanted human NSCs in the brains of mice effectively reduce Tau phosphorylation levels [74].…”
Section: Stem Cell Treatment For Alzheimer 'S Diseasementioning
confidence: 90%
“…Neural stem cells (NSCs) are another possible candidate for Alzheimer's disease. When NSCs are transplanted, they have the potential to renew deteriorated cholinergic neurons, and new neurons originating from NSCs can establish synaptic links with nearby neurons [32]. The utilization of NSCs to replace and rehabilitate impaired cholinergic neurons and neural connections in the brain presents another theoretical avenue for exploring treatment possibilities for Alzheimer's disease [32].…”
Section: Stem Cell Alternative Treatment Possibilitymentioning
confidence: 99%
“…NSCs have been considered to possess valuable potential to treat cerebral diseases for which present therapies are almost unavailable due to their ability to differentiate into neurons and glial cells or their paracrine mechanisms. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…NSCs stimulate endogenous synaptogenesis, which improves cognition. However, it is challenging to correctly characterize NSCs' positive effects in AD 41 …”
Section: Diseases Amenable To Cell‐based Therapiesmentioning
confidence: 99%